Sustainability Transition Towards a Bio-Based Economy: New Technologies, New Products, New Policies - Piergiuseppe Morone (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book proposes an array of 11 key papers aimed at investigating the complex and multifaceted nature of the bio-based economy, focusing both on a conceptual understanding of the transition and on the measurement issues associated with it. More specifically, the papers included in this book can be broadly divided in two groups: (1) those aiming at adding to our understanding of the transition process towards a sustainable bio-based economy; and (2) those aiming at adding to the definition and measurement of the emerging sustainable bio-based economy. The book offers a comprehensive view of the phenomenon, providing a logical framework for understanding the ongoing transition towards a bio-based economy, as well as an overview of existing tools to assess and measure it. Policy-makers will largely benefit from the book, which contributes to taking a further step towards the much-needed transition to sustainability.